Global Prevalence of Colistin- and Carbapenem-Resistant Gram-Negative Organisms: SMART 2015–2016. (4th October 2017) - Lob, Sibylle; Hackel, Meredith; Badal, Robert; Young, Katherine; Motyl, Mary; Sahm, Dan
Abstract: Background: Antimicrobial resistance is spreading worldwide, including acquired resistance to carbapenems, requiring the increasing use of older agents like colistin (CST). In this study, we analyzed the global prevalence of carbapenem-resistant (CR) Gram-negative clinical isolates that were also resistant to CST. Methods: In 2015–2016, 170 hospitals in 53 countries collected consecutive Gram-negative aerobic or facultative bacilli from intra-abdominal, urinary, and respiratory tract infections. MICs were determined for 45, 126 non- Proteeae non- Serratia Enterobacteriaceae (NPSE) and 11, 026 P . A eruginosa (PA) isolates using CLSI broth microdilution. As our interest was in acquired resistance, Proteeae and Serratia spp. were excluded due to intrinsic non-susceptibility to imipenem and/or CST. The percentage susceptible was assessed using CLSI breakpoints where available. EUCAST was used for CST against NPSE. Isolates with MICs above the CLSI S breakpoint for imipenem were defined as CR. Results: Globally, 4.2% of NPSE were CR, of which 19.9% were CST-R, for a total of proportion of CST-R CR NPSE of 0.8%. Among PA, 30.0% were CR, of which 0.8% were CST-R, for an overall proportion of CST-R CR PA of 0.2%. Regional prevalence of CST-R CR NPSE and PA isolates is shown in the table Conclusion: Combined resistance to carbapenems and colistin was rare in P . A eruginosa, but was detected in a small yet significant proportion of NPSE, especially from Europe and the Middle East, where almost 30% of CR NPSE were also CST-R. New antimicrobial agents with activity against multidrug-resistant isolates are needed. Disclosures: M. Hackel, IHMA: Employee, Salary. R. Badal, IHMA, Inc.: Employee, Salary. K. Young, Merck: Employee and Shareholder, Dividends and Salary. M. Motyl, Merck & Co., Inc.: Employee, Salary